Knowledge, attitudes, and practices of the general population, herpes zoster patients, and dermatologists toward herpes zoster in China: A quantitative cross-sectional survey - Chun Chang; Haiwen Tang; Xin Zhang; Chenguang Zhu; Yang Feng; Chiyu Ye (Human Vaccines & Immunotherapeutics)
The burden of herpes zoster (HZ) is anticipated to increase among the aging population of China over time. The knowledge, attitudes, and practices (KAP) of the population toward HZ can help inform the design of public health strategies. As there is a paucity of KAP data in China, this cross-sectional survey therefore sought to assess KAP related to HZ from the general population, patients with HZ, and dermatologists in China. The total number of respondents from the general population, HZ patients, and dermatologists were 804, 282, and 160, respectively. Notably, some gaps in knowledge regarding the severity, transmission, and prevention of HZ were identified across all groups. For example, less than half of respondents from the general population and HZ patients understood that vaccination does not treat HZ. For dermatologists, not all were aware of adverse reactions following HZ vaccination and some had misconceptions regarding the mode of transmission of HZ. Given the link between an individual’s disease knowledge to their attitudes and practices, improved understanding of HZ could underlie positive attitudes and help reinforce healthcare professionals’ recommendations in the management and prevention of HZ. In particular, doctors may be well-positioned to support HZ prevention initiatives, as most of the general population and HZ patients found vaccination more acceptable if recommended by a doctor (78.9% and 81.6%, respectively). Therefore, consideration of these KAP attributes may support the development of targeted educational interventions and effective public health strategies against HZ in China.